Serum adiponectin in patients with coronary heart disease - Parul, SS; Mazumder, M; Debnath, BC; Haque, ME (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):78-82 The abstract of this article is available on the PubMed website